Evaluation of shoot-growth variation in diverse carrot (Daucus carota L.) germplasm for genetic improvement of stand establishment - Loarca, Jenyne; Liou, Michael; Dawson, Julie C.; Simon, Philipp W. (Frontiers in Plant Science, 2024)
Carrot (Daucus carota L.) is a high value, nutritious, and colorful crop, but delivering carrots from seed to table can be a struggle for carrot growers. Weed competitive ability is a critical trait for crop success that carrot and its apiaceous relatives often lack owing to their characteristic slow shoot growth and erratic seedling emergence, even among genetically uniform lines. This study is the first field-based, multi-year experiment to evaluate shoot-growth trait variation over a 100-day growing season in a carrot diversity panel (N=695) from the United States Department of Agriculture National Plant Germplasm System. This study provides the first broad-sense heritability estimates for early-season seedling vigor (0.68